Pregravid preparation and pregnancy management of women with endometriosis in the in vitro fertilization program: a clinical case - Faina K. Tetelyutina; Olga V. Shestakova; Olga N. Dolgova; Liudmila M. Shirobokova (IP Berlin A.V., 2020)
The presented clinical case of a patient with infertility and a combination of various forms of endometriosis was the basis for discussing the optimal choice of tactics for managing these patients.